Preliminary Evidence from a Psychoeducational Webinar to Support Work Resilience among Mining Employees in Geographically Remote Areas - Friska Juliana Putri Saragih; Yulia Ayriza; Rosita Endang Kusmaryani; Komang Tri Meika Sari (Da'wa Faculty of Islamic State University Salatiga, 2026)
Employees working in geographically remote mining areas face substantial psychological challenges related to complex job demands, limited social interaction, and isolation. In this context, work resilience represents an important psychological resource. This pilot study explored the feasibility of delivering a brief positive psychology–based psychoeducational webinar and examined preliminary patterns in self-reported work resilience. A quasi-experimental one-group pre-test–post-test design was applied. Although 40 employees attended the webinar, analyses were conducted using complete paired data from 20 participants. Work resilience was assessed using an exploratory dichotomous self-report questionnaire administered before and after the intervention. Descriptive analyses indicated an overall upward shift in post-test scores, with individual variability. A Wilcoxon signed-rank test suggested a statistically significant difference between measurement occasions (p = 0.040). Given the exploratory design and absence of a control group, findings are interpreted cautiously and do not imply intervention effectiveness. Overall, the results provide preliminary descriptive evidence supporting the feasibility of webinar-based psychoeducational delivery in geographically remote industrial settings.